DDEL-04. BIOMATERIAL SCAFFOLDS FOR THE DELIVERY OF NEURAL STEM CELL THERAPIES INTO THE GLIOBLASTOMA RESECTION CAVITY. (14th November 2022) - Bomba, Hunter; Kass, Lauren; Carey-Ewend, Abigail; Sheets, Kevin; Valdivia, Alain; Goetz, Morgan; Findlay, Ingrid; Mercer-Smith, Alison; Khagi, Simon; Hingtgen, Shawn
Abstract: Therapeutic neural stem cells (tNSCs) are a promising new platform for the treatment of glioblastoma (GBM). tNSCs exhibit a characteristic known as tumor tropism, in which they can migrate towards distant GBM foci via cytokine signaling. Complementarily, genetic engineering of NSCs may be performed to turn the cells into drug-producing therapeutics. Together, this results in NSCs that act as targeted drug delivery vehicles that can seek out and kill invasive GBM lesions post-resection. However, one limitation of this cell therapy platform is that tNSCs delivered directly into the GBM resection cavity are rapidly cleared. We hypothesized that the commercially available, FDA-approved hemostat FLOSEAL® may be used as a drug delivery system for improving cell persistence in the brain, thus resulting in improved therapeutic efficacy. It was found that tNSCs encapsulated in FLOSEAL® were detectable in the brain for over 95 days in mice, a drastic improvement compared to directly injected cells and cells encapsulated in other existing hemostat systems, which persisted 2 weeks or less. However, two in vivo efficacy studies of tNSCs encapsulated in FLOSEAL® yielded contrasting results. While the FLOSEAL®-tNSC system was significantly more efficacious against a GBM8 tumor model in mice compared to directly injected tNSCs, it was not significantly more effective against a U87 tumor model. This could be due to a variety of factors, including the tumor type (diffuse vs. solid for GBM8 and U87, respectively) and negative impacts of FLOSEAL® on tNSC markers of proliferation, migration, drug production, and anti-apoptosis. While FLOSEAL® is a promising material for the delivery of tNSCs in the treatment of post-operative GBM, alternative systems that allow for improved persistence while maintaining the therapeutic activity of the cells would be optimal for long-term treatment with tNSCs.